Edmunda Wnuka-Lipińskiego ujęcie konfliktu wartości i interesów - Dobrogowska, Monika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The article presents an axiological-pragmatic research perspective applied by Edmund Wnuk-Lipiński in the context of Polish society. On the basis of the considerations carried out, the categories of values are, in his opinion, the desirable states of the political community or individuals established in a given cultural tradition, while interests refer to the pragmatic sphere and denote a situation the achievement of which is advantageous from some point of view. The author investigated conflicts occurring between different values, between interests, as well as between values and interests. Particularly interested in the phases of radical social change, Wnuk-Lipiński presented them based primarily on the preferences of Polish society for specific values and interests. He also applied the axiological-pragmatic perspective to the study of contemporary Polish attitudes and behaviour.